Short-Range Structure of Amorphous Calcium Hydrogen Phosphate - Lu, B.Q.; Garcia, Natalya; Chevrier, D.M.; Zhang, P.; Raiteri, Paolo; Gale, Julian; Gebauer, D. (AMER CHEMICAL SOC, 2019)
Copyright © 2019 American Chemical Society. Calcium orthophosphates (CaPs) are the hard constituents of bones and teeth, and thus of ultimate importance to humankind, while amorphous CaPs (ACPs) may play crucial roles in CaP biomineralization. Among the various ACPs with Ca/P atomic ratios between 1.0-1.5, an established structural model exists for basic ACP (Ca/P = 1.5), while those of other ACPs remain unclear. Herein, the structure of amorphous calcium hydrogen phosphate (ACHP; Ca/P = 1.0) obtained via aqueous routes at near-neutral pH values, without stabilizers, was studied by experiments (mainly, TEM with ED, XRD, IR, and NMR spectroscopies, as well as XAS) and computer simulation. Our results globally show that ACHP has a distinct short-range structure, and we propose calcium hydrogen phosphate clusters (CHPCs) as its basic unit. This model is consistent with both computer simulations and the experimental results, where CHPCs are arranged together with water molecules to build up ACHP. We demonstrate that Posner's clusters, which are conventionally accepted to be the building unit of basic ACPs, do not represent the short-range structure of ACHP, as Posner's clusters and CHPCs are structurally distinct. This finding is important not only for the determination of the structures of diverse ACPs with varying Ca/P atomic ratios but also for fundamental understanding of a major mineral class that is central to biomineralization in vertebrates and, thus, humans, in particular. ©